2021
DOI: 10.1021/acs.analchem.1c02026
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen–Deuterium Exchange Desorption Electrospray Ionization Mass Spectrometry Visualizes an Acidic Tumor Microenvironment

Abstract: We report that microdroplet hydrogen−deuterium exchange (HDX) detected by desorption electrospray ionization mass spectrometry imaging (DESI-MSI) allows the measurement of the acidity of a tissue sample. The integration of HDX and DESI-MSI has been applied to visualize the acidic tumor microenvironment (TME). HDX-DESI-MSI enables the simultaneous collection of regional pH variation and its corresponding in-depth metabolomic changes. This technique is a cost-effective tool for providing insight into the pH-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…Only a few microliters of methanol-water solvent suffice to desorb and ionize a wide range of metabolites within a few seconds. In other studies, we have also shown that the transient process of microdroplet HDX can be well captured by a DESI-MS system [29]. In this study, a proportion of methanol-deuterium water is used as the desorption solvent in CPSI-MS.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Only a few microliters of methanol-water solvent suffice to desorb and ionize a wide range of metabolites within a few seconds. In other studies, we have also shown that the transient process of microdroplet HDX can be well captured by a DESI-MS system [29]. In this study, a proportion of methanol-deuterium water is used as the desorption solvent in CPSI-MS.…”
Section: Introductionmentioning
confidence: 81%
“…Urea ([2M+H] + ) and creatinine ([M+H] + ) were the most typical ones because their isotope peak intensity differences between the two groups were so obvious to be directly read out from the average mass spectra (Figure 6B). It is probably originated from the different pH environments [29].…”
Section: Creating New Dimension and Features For Metabolic Profilingmentioning
confidence: 99%
See 1 more Smart Citation
“…The abundance of ten amino acids, four nucleotides, nucleobases, lactate and vitamin E varies in renal cell carcinomas, and normal tissue was obtained with the help of LARESI-MSI and tandem mass spectrometry. In 2021, Song et al reported a new MSI technique called hydrogendeuterium exchange DESI MSI (HDX-DESI-MSI) to detect the pH value and visualize the acidic tumor microenvironment (TME) (Figure 7B) [120]. In this work, methanol-D 2 O was used as the spray solvent of DESI and a xenograft tumor was roughly divided into three microregions with different pH values, including 6.4 ± 0.2, 6.8 ± 0.2 and 7.2 ± 0.2.…”
Section: Metabolitesmentioning
confidence: 99%
“…12,13 Moreover, in situ detection can display the distribution of target molecules in the whole plant tissue and reveal the transport routes of nutrients during metabolism. Generally, the sampling methods in the field of mass spectral analysis of plant ingredients mainly include desorption electrospray ionization (DESI), 14 plasma-jet, 15 and methods based on laser technology including laser ablation-dielectric barrier discharge ionization (LA-DBDI), 16 laser ablation-electrospray ionization (LA-ESI) 17 and laser desorption ionization (LDI). 18 Matrix-assisted laser desorption/ionization-mass spectrometry (MALDI-MS) has long been used in in situ detection of biological macromolecules in animal and plant tissues, such as proteins, polysaccharides, lipids, metabolites and other biological macromolecules.…”
Section: Introductionmentioning
confidence: 99%